Toward Reproducible Acoustic Voice Measurements During Laryngeal Videoendoscopy, With Emphasis on Microphones Mounted on Cameras and Rigid Laryngoscopes. - Švec, Jan G.; Valášková, Dominika (Journal of Speech, Language & Hearing Research, 2026)
Purpose: Glottal adjustments and vocal fold oscillations change with the vocal intensity, pitch, and quality. Therefore, capturing and recording vocal sounds during laryngoscopy is desirable. Here, we show how camera-mounted or endoscope-mounted microphones can be comfortably used to maintain a reasonably stable mouth-to-microphone (MTM) distance and obtain reproducible acoustic measures of voice during rigid laryngoscopy. Method: We took advantage of recently obtained data on the depth of insertion of rigid laryngoscopes into the oral cavity in adult male and female subjects. Using this as a reference, we offer an empirical formula for determining the representative MTM distance in adults for 90° and 70° rigid laryngoscopes to which a microphone is fixed. The uncertainty in sound pressure level (SPL) due to inter-individual variations in laryngoscope insertion was determined using standard equations for sound radiation. Results: When microphones are mounted on the camera head or on the laryngoscope at positions 15-40 cm from the laryngoscope tip, the resulting representative MTM distances range from 5 to 33 cm. Once the representative MTM distances exceed 9 cm, the expected inherent SPL inaccuracy of the setup is less than ±2 dB, and the expected average male-to-female SPL differences are below 1 dB with 95% confidence. Conclusions: When the vocal sound is captured using a microphone fixed to a rigid laryngoscope at an MTM distance greater than 9 cm, the influence of inter-individual differences in laryngoscope insertion on the acoustic voice signal can be neglected. To minimize the influence of ambient noise and room acoustics, MTM distances greater than 30 cm are not recommended. Calibration ensures SPL accuracy and reproducibility.